Lidar com a complexidade do racismo: perspetivas dos professores em contextos multiculturais de ensino primário em Tessalónica/Grécia (Revista Lusófona de Educação, 2025)
Teachers have a crucial role in dealing with the complexity of racism by acting as role models and employing various teaching practices that promote human rights, respect, equality, and intercultural understanding among all students. The aim of the present qualitative research, which was conducted using semi-structured interviews with 20 participants,was to explore primary teachers’ perspectives on racism in school settings and their responses on counteraction. Data were analysed by thematic analysis. Findings highlighted that racism manifests in various forms, driven by stereotypical and discriminatory perceptions toward various forms of difference. Racial manifestations are visible in various school settings and have negative effects, primarily microaggressions, discrimination, and exclusion. Teachers employ various teaching practices to foster democratic values, equality, interculturalunderstanding and social inclusion. Teachers’ training in multicultural education and collaboration with parents can also address racism more effectively. A holistic school policy was identified as a solution for creating safe and inclusive learning environments.Keywords: racism; school violence; social justice; Primary Education